Negative active material, negative pole piece, battery and electric device
By adjusting the particle size distribution of the negative electrode active material, the lithium ion diffusion ability is improved, and the problem of poor battery fast charging capacity in low-temperature environments is solved, and significant charging performance is achieved.
Patent Information
- Application Number
- CN202311641387.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-30
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-11-30
AI Technical Summary
In low temperature environments, the battery has poor fast charging capabilities and usually requires a longer charging time.
By adjusting the volume average particle size Dv50 and volume distribution particle size Dv1 of the negative electrode active material, it can improve the diffusion ability of lithium ions in the negative electrode active material and the negative electrode film layer, and slow down the side reaction between the negative electrode active material and the electrolyte solution.
It significantly improves the charging capacity under low temperature conditions and improves the battery's low-temperature fast charging performance.
Smart Images

Figure CN119833580A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a negative electrode active material, a negative electrode plate, a battery and an electrical device. Background Art
[0002] Batteries are widely used because of their reliable performance, no pollution, and no memory effect. For example, as environmental protection issues are increasingly valued and new energy vehicles become more popular, the demand for power battery cells will show explosive growth.
[0003] As the application range of batteries becomes wider and wider, the requirements for battery performance are becoming increasingly stringent. In a relatively low temperature environment, the battery's fast charging ability is poor and usually requires a longer charging time. Summary of the invention
[0004] The present application provides a negative electrode active material, a negative electrode plate, a battery and an electrical device. When the negative electrode active material is applied to a battery, the low-temperature fast charging capability of the battery can be improved.
[0005] In a first aspect, the present application provides a negative electrode active material, the negative electrode active material comprising artificial graphite particles and a carbon layer disposed on at least a portion of the surface of the artificial graphite particles, wherein the volume average particle size D of the negative electrode active material is v 50 satisfies: 3μm≤Dv50≤7μm; volume distribution particle size D of negative electrode active material v 1 Satisfaction: D v 1≤1.5μm.
[0006] Therefore, the embodiment of the present application adjusts the D of the negative electrode active material. v 50 and D v 1. It can simultaneously improve the diffusion capacity of lithium ions in the negative electrode active material and the negative electrode film layer, and can slow down the side reactions between the negative electrode active material and the electrolyte, which is beneficial to significantly improve the charging capacity under low temperature conditions.
[0007] In some embodiments, 0.8 μm ≤ D v 1≤1.5μm; optionally, 0.9μm≤D v 1≤1.3μm; further optionally, 0.9μm≤D v 1≤1.0μm. The volume particle size distribution of the negative electrode active material is further regulated by D v 1. It can further regulate the proportion of fine powder. The active material contains an appropriate amount of fine powder, which is beneficial to further improve the charging efficiency under low temperature conditions.
[0008] In some embodiments, D v 99≤18μm; optionally, 12μm≤D v99≤18μm. By analyzing the volume particle size distribution D v 99 further selection can further improve the low-temperature charging performance of the battery cells.
[0009] In some embodiments, the negative electrode active material includes primary particles, and the number of primary particles in the negative electrode active material accounts for ≥90%; optionally ≥95%. The secondary particles have a smaller particle size, which is beneficial to further shorten the migration path of lithium ions and improve the low-temperature fast charging capability of the battery cell.
[0010] In some embodiments, the gram capacity of the negative electrode active material is 330 mAh / g to 340 mAh / g. The gram capacity of the negative electrode active material is relatively high, and the energy density of the battery cell is high. On the basis of this high energy density, the negative electrode active material can also simultaneously improve the fast charging capability of the battery cell.
[0011] In some embodiments, the tap density of the negative electrode active material is 0.78 g / cm 3 Up to 1.2g / cm 3 ; Optional: 0.9g / cm 3 Up to 1.1g / cm 3 The tap density of the negative electrode active material is within the above range, which enables good contact between particles in the negative electrode film layer, and is beneficial to improving the fast charging capability of the battery cell; due to the close packing between the particles, the energy density of the battery cell can also be improved.
[0012] In some embodiments, the degree of graphitization of the artificial graphite particles is 90% to 93%, and optionally 91% to 93%. When the degree of graphitization of the artificial graphite particles is within the above range, the particle structure can have a larger interlayer spacing and a lower powder resistance, which can further improve the fast charging capability of the battery cell.
[0013] In some embodiments, the average thickness of the carbon layer is ≥ 2 nm, and can be 2 nm to 20 nm. By coating the surface of the artificial graphite particles with a carbon layer, the low-temperature fast charging performance of the battery cell can be further improved.
[0014] In a second aspect, the present application proposes a negative electrode plate, which includes a negative electrode collector and a negative electrode film layer arranged on at least one side of the negative electrode collector, the negative electrode film layer includes a negative electrode active material, and the negative electrode active material includes the negative electrode active material of any embodiment of the first aspect of the present application.
[0015] In a third aspect, the present application proposes a battery, comprising a positive electrode plate as in any embodiment of the second aspect of the present application.
[0016] In a fourth aspect, the present application proposes an electrical device, including a battery as in any embodiment of the third aspect of the present application, wherein the battery is used to provide electrical energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments of the present application will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without paying creative work.
[0018] Figure 1 It is a schematic diagram of an embodiment of a battery cell of the present application.
[0019] Figure 2 yes Figure 1 An exploded schematic diagram of an embodiment of a battery cell.
[0020] Figure 3 It is a schematic diagram of an embodiment of a battery module of the present application.
[0021] Figure 4 It is a schematic diagram of an embodiment of the battery pack of the present application.
[0022] Figure 5 yes Figure 4 An exploded schematic diagram of an embodiment of a battery pack is shown.
[0023] Figure 6 It is a schematic diagram of an embodiment of an electric device including the battery cell of the present application as a power source.
[0024] Figure 7 This is one of the scanning electron microscope (SEM) images of the negative electrode active material in Example 1 of the present application.
[0025] Figure 8 This is the second scanning electron microscope (SEM) picture of the negative electrode active material in Example 1 of the present application.
[0026] The following are the descriptions of the reference numerals:
[0027] 1. Battery pack; 2. Upper box; 3. Lower box; 4. Battery module;
[0028] 5. Battery cell; 51. Housing; 52. Electrode assembly;
[0029] 53. Cover plate;
[0030] 6. Electrical equipment. DETAILED DESCRIPTION
[0031] Below, the embodiments of the negative electrode active material, negative electrode sheet, battery cell, battery and electrical device of the present application are specifically disclosed in detail with appropriate reference to the drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0032] "Scope" disclosed in the present application is defined in the form of lower limit and upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a particular range. The scope defined in this way can be inclusive or exclusive of end values, and can be arbitrarily combined, i.e., any lower limit can be combined with any upper limit to form a range. For example, if a range of 60 to 120 and 80 to 110 is listed for a particular parameter, it is understood that a range of 60 to 110 and 80 to 120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following range can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In the present application, unless otherwise specified, the numerical range "a to b" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0 to 5" means that all real numbers between "0 to 5" are listed in this document, and "0 to 5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0033] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0034] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0035] If there is no special explanation, all steps S of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps S(a) and (b), which means that the method may include steps S(a) and (b) performed sequentially, or may include steps S(b) and (a) performed sequentially. For example, it is mentioned that the method may also include step S(c), which means that step S(c) can be added to the method in any order. For example, the method may include steps S(a), (b) and (c), or may include steps S(a), (c) and (b), or may include steps S(c), (a) and (b), etc.
[0036] The battery cell includes a positive electrode plate, a negative electrode plate and a separator. During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode plate and the negative electrode plate through the electrolyte. The negative electrode plate includes a negative electrode collector and a negative electrode film layer arranged on at least one side of the negative electrode collector. The negative electrode active material contained in the negative electrode film layer is an important component of the battery cell, and the active ions can be embedded in and released from the negative electrode active material.
[0037] Under low temperature conditions, the conductivity of the electrolyte decreases, and the solid electrolyte interface (SEI) membrane impedance, charge transfer impedance, and diffusion impedance of active ions in the negative electrode plate will increase, resulting in enhanced polarization, which makes the low-temperature performance of the battery cell poor. The negative electrode plate is a key factor restricting the low-temperature kinetic performance of the battery cell. In order to improve the low-temperature kinetic performance of the battery cell, it is usually considered to improve the performance of the negative electrode film layer, such as adjusting the thickness of the negative electrode film layer, reducing the compaction density of the negative electrode film layer, etc., but the above methods have limited improvement on the kinetic performance of the battery cell during charging.
[0038] In view of the above problems, the embodiment of the present application provides a negative electrode active material, which is regulated by adjusting the particle size distribution of the negative electrode active material, specifically adjusting the volume average particle size D of the negative electrode active material. v 50 and D v 1. The dynamic performance of the battery cell in the early and late stages of charging can be significantly improved, and the battery cell can be quickly charged. Next, the implementation of the present application is described in detail.
[0039] Negative electrode active material
[0040] In a first aspect, an embodiment of the present application provides a negative electrode active material.
[0041] The negative electrode active material includes artificial graphite particles and a carbon layer disposed on at least a portion of the surface of the artificial graphite particles.
[0042] The volume average particle size D of the negative electrode active material v50Satisfy: 3μm≤D v 50≤7μm,
[0043] Volume particle size distribution of negative electrode active materials D v 1 Satisfaction: D v 1≤1.5μm.
[0044] When the negative electrode active material meets the above particle size distribution conditions, it can improve both the fast charging performance under low temperature conditions and the high temperature cycle performance. The possible reasons are as follows:
[0045] Battery cell charging is the process in which active ions such as lithium ions and sodium ions are extracted from the positive electrode active material and embedded in the negative electrode active material. In the field of batteries, the industry often uses the "state of charge (SOC)" to reflect the capacity of the battery after charging. Its numerical value is defined as the percentage of the existing capacity to the capacity of the battery after full charge, and the value range is 0 to 100%. When "SOC = 0", it means that the battery is not charged, when "SOC = 100%", it means that the battery is in a fully charged state, and when "0 < SOC < 100%", it means that the battery has been charged and has a certain capacity, but has not been fully charged. In the implementation of the present application, the early stage of charging is defined as a low SOC state (≤ 30% SOC), and the late stage of charging is defined as a high SOC state (≥ 60% SOC).
[0046] At low temperatures, the diffusion rate of active ions such as lithium ions between graphite layers is slow, and the kinetic process of lithium ion embedding in the negative electrode is relatively slow. The slow kinetics lead to overpotential, making the actual potential of graphite lithium embedding close to the potential of lithium metal deposition, which easily leads to lithium deposition during low-temperature charging and deteriorates the low-temperature charging performance of battery cells.
[0047] The volume average particle size D of the negative electrode active material v 50 is the particle size corresponding to when the cumulative volume distribution percentage of the negative electrode active material reaches 50%, and the volume average particle size D of the negative electrode active material v When 50 is 3μm to 7μm, the particle size of the negative electrode active material is small, the active area is large, and the active lithium insertion sites are more. The number of lithium ions diffused to the surface of the negative electrode active material increases, and the interface reaction rate of the negative electrode active material is accelerated, which is beneficial to improve the kinetic performance of the battery cell at a low SOC state, thereby improving its fast charging capability. When the battery cell is in a high SOC state, the diffusion rate of lithium ions becomes the limiting step of the charging rate. The negative electrode active material with a small particle size shortens the lithium insertion path and accelerates the diffusion rate of lithium ions inside the negative electrode active material, which can reduce polarization and is beneficial to the low temperature performance of the battery cell. Therefore, the embodiment of the present application adjusts the volume average particle size D v 50 can regulate the diffusion channels and diffusion rates of lithium ions on the surface and inside of the negative electrode active material.
[0048] However, only regulating the diffusion capacity of lithium ions in the negative electrode active material cannot effectively improve the low temperature charging performance of the battery. It is also necessary to simultaneously regulate the diffusion capacity of lithium ions in the negative electrode film layer. v 50, also synchronizes and regulates D v 1. Volume particle size distribution D of negative electrode active materials v 1 is the particle size corresponding to the cumulative volume distribution percentage of the negative electrode active material reaching 1%, and D v 1. It can affect the proportion of fine powder in the negative electrode active material by adjusting D v 1≤1.5μm, the negative electrode active material contains an appropriate amount of fine powder, which is beneficial to improve the charging power under low temperature conditions and the active surface of the negative electrode active material will not be too much, which can slow down the side reaction between the negative electrode active material and the electrolyte. In addition, the agglomeration risk of the negative electrode active material in the negative electrode film layer is low, which can improve the porosity in the negative electrode film layer and facilitate the diffusion of lithium ions in the negative electrode film layer. In the embodiment of the present application, fine powder refers to particles with relatively small particle size.
[0049] Therefore, the embodiment of the present application adjusts the D v 50 and D v 1. It can simultaneously improve the diffusion capacity of lithium ions in the negative electrode active material and the negative electrode film layer, and can slow down the side reactions between the negative electrode active material and the electrolyte, which is beneficial to significantly improve the charging capacity under low temperature conditions.
[0050] In some embodiments, the volume particle size distribution D of the negative electrode active material is v 99 Satisfied: D v 99≤18μm.
[0051] In addition to regulating the D of the negative electrode active material, the present invention also provides a method for controlling the D of the negative electrode active material. v 50 and D v 1. D can also be further regulated v 99, Volume particle size distribution of negative electrode active material D v 99 is the particle size corresponding to the cumulative volume distribution percentage of the negative electrode active material reaching 99%. v 99 can basically control the upper limit of the particle size of the negative electrode active material, and the volume particle size distribution of the negative electrode active material D v 99 Satisfy D v99≤18μm, the upper limit of the particle size of the negative electrode active material is small, and the consistency of the lithium insertion degree of the negative electrode active materials with different particle sizes is improved due to the small difference in particle size, and the polarization degree of the negative electrode plate is further reduced; and by regulating the overall particle size of the negative electrode active material, the negative electrode film layer has a better pore distribution, which can accelerate the diffusion speed of lithium ions in the negative electrode film layer, thereby improving the low-temperature charging performance of the battery cell. In the embodiment of the present application, D v When 99≤18μm, the coating performance of the negative electrode slurry can also be improved. The performance of the negative electrode film layer coated with the negative electrode slurry is more consistent, and it is not easy to produce scratches when thinly coated, which can avoid subsequent interface abnormalities and performance deterioration caused by scratches.
[0052] In summary, the embodiment of the present application further simultaneously adjusts the volume average particle size D of the negative electrode active material. v 50. D v 1 and D v 99, which increases the number of active sites on the surface of the negative electrode active material and the channels for lithium ion diffusion; since the lithium ion diffusion path is shorter, its diffusion rate is improved; and the consistency of the lithium insertion degree between the particles is improved, and the polarization degree of the negative electrode plate is reduced; and the diffusion capacity of lithium ions in the negative electrode film layer is improved, thereby significantly improving the kinetic performance of the battery cell in the early and late stages of charging, and improving the low-temperature fast charging capability of the battery cell.
[0053] The volume average particle size D of the negative electrode active material v 50Satisfy: 3μm≤D v 50≤7μm, D v 50 can be 3 μm, 3.2 μm, 3.5 μm, 3.8 μm, 4 μm, 4.2 μm, 4.5 μm, 4.8 μm, 5 μm, 5.2 μm, 5.5 μm, 5.8 μm, 6 μm, 6.2 μm, 6.5 μm, 6.8 μm, 7 μm or a range consisting of any two of the above values. v 50 is further selected to further improve the low-temperature charging performance of the battery cell.
[0054] Volume particle size distribution of negative electrode active materials D v 1 Satisfaction: D v 1≤1.5μm, D v 1 can specifically be 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, or a range consisting of any two of the above values. Optionally, 0.8 μm ≤ D v 1≤1.5μm; further optionally, 0.9μm≤D v1≤1.3μm; further optionally, 0.9μm≤D v 1≤1.0μm. The volume particle size distribution of the negative electrode active material is further regulated by D v 1. It can further regulate the proportion of fine powder. The active material contains an appropriate amount of fine powder, which is beneficial to further improve the charging efficiency under low temperature conditions.
[0055] Volume particle size distribution of negative electrode active materials D v 99 Satisfied: D v 99≤18μm, D v 99 may specifically be 10 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.5 μm, 16 μm, 16.5 μm, 17 μm, 17.5 μm, 18 μm, or a range consisting of any two of the above values. Optionally, 12 μm≤D v 99≤18μm. By analyzing the volume particle size distribution D v 99 further selection can further improve the low-temperature charging performance of the battery cells.
[0056] In some embodiments, the negative electrode active material includes primary particles.
[0057] Optionally, the number of primary particles in the negative electrode active material accounts for ≥90%; optionally ≥95%; optionally ≥98%; optionally ≥99%. When the number of primary particles in the negative electrode active material accounts for 100%, it means that the negative electrode active material is composed of primary particles. The small particle size of primary particles is conducive to further shortening the migration path of lithium ions and improving the low-temperature fast charging capability of battery cells.
[0058] In some embodiments, the gram capacity of the negative electrode active material is 330 mAh / g to 340 mAh / g. The gram capacity of the negative electrode active material is relatively high, and the energy density of the battery cell is high. On the basis of this high energy density, the negative electrode active material can also simultaneously improve the fast charging capability of the battery cell.
[0059] Illustratively, the gram capacity of the negative electrode active material can be 330 mAh / g, 331 mAh / g, 332 mAh / g, 333 mAh / g, 334 mAh / g, 335 mAh / g, 336 mAh / g, 337 mAh / g, 338 mAh / g, 339 mAh / g, 340 mAh / g, or a range consisting of any two of the above values.
[0060] In some embodiments, the tap density of the negative electrode active material is 0.78 g / cm 3 Up to 1.2g / cm 3; Optional: 0.9g / cm 3 Up to 1.1g / cm 3 The tap density of the negative electrode active material is within the above range, which enables good contact between particles in the negative electrode film layer, and is beneficial to improving the fast charging capability of the battery cell; due to the close packing between the particles, the energy density of the battery cell can also be improved.
[0061] For example, the tap density of the negative electrode active material may be 0.78 g / cm 3 , 0.8g / cm 3 , 0.82g / cm 3 , 0.85g / cm 3 , 0.88g / cm 3 , 0.9g / cm 3 、0.92g / cm 3 , 0.95g / cm 3 、0.98g / cm 3 , 1g / cm 3 , 1.05g / cm 3 , 1.10g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 Or a range consisting of any two of the above values.
[0062] In some embodiments, the degree of graphitization of the artificial graphite particles is 90% to 93%; optionally 91% to 93%. For example, the degree of graphitization of the artificial graphite particles is 90%, 90.5%, 91%, 91.5%, 92%, 92.5%, 93%, or a range consisting of any two of the above values. When the degree of graphitization of the artificial graphite particles is within the above range, the particle structure can have a larger interlayer spacing and a lower powder resistance, which can further improve the fast charging capability of the battery cell.
[0063] Artificial graphite particles are formed by high-temperature heat treatment of a carbon source. The order of arrangement of carbon atoms in the carbon source may be poor, and it is mainly an ordered arrangement in two-dimensional space, that is, a chaotic layer structure. After high-temperature heat treatment, the disordered or two-dimensional ordered arrangement is transformed into an ordered arrangement in three-dimensional space, that is, amorphous carbon is transformed into graphite. The process of ordering of atomic arrangement is the graphitization process, and the degree of ordering transformation is the degree of graphitization, which can be measured by X-ray diffraction.
[0064] At least part of the surface of the artificial graphite particles is coated with a carbon layer, which mainly includes amorphous carbon. Amorphous carbon refers to carbon materials in a non-completely crystalline amorphous region or an amorphous solid. The lattice structure of amorphous carbon tends to be disordered, while the lattice structure of artificial graphite particles tends to be orderly, which can be observed and distinguished by transmission electron microscopy TEM. By coating the surface of artificial graphite particles with a carbon layer, the low-temperature fast charging performance of battery cells can be further improved.
[0065] In some embodiments, the coverage of the carbon layer on the surface of the artificial graphite particles is ≥50%, and can be 60% to 100%. When the coverage of the carbon layer on the surface of the artificial graphite particles is 100%, it can be understood that the carbon layer covers the entire surface of the artificial particles; when the coverage of the carbon layer on the surface of the artificial graphite particles is <100%, it can be understood that the carbon layer covers part of the surface of the artificial particles.
[0066] In some embodiments, the average thickness of the carbon layer is ≥ 2 nm, and may be 2 nm to 20 nm; for example, 2 nm to 15 nm, 2 nm to 10 nm, or 5 nm to 10 nm.
[0067] In the embodiment of the present application, D of the negative electrode active material v 99.D v 50. D v 1 The detection can be carried out using equipment and methods known in the art. For example, a certain amount of negative electrode active material is taken as a sample, and the volume average particle size D is measured by a Mastersizer 2000E laser particle size analyzer according to the test standard GB / T19077-2016. v 50 and volume particle size distribution D v 99 and volume particle size distribution D v 1, where D v 99 is the particle size corresponding to when the cumulative volume distribution percentage of the negative electrode active material reaches 99%; D v 50 is the particle size corresponding to the cumulative volume distribution percentage of the negative electrode active material reaching 50%; D v 1 is the particle size corresponding to the cumulative volume distribution percentage of the negative electrode active material reaching 1%.
[0068] In the embodiment of the present application, the prepared negative electrode active material can be directly taken as a sample for testing, or the negative electrode active material can be prepared into a negative electrode sheet, and the negative electrode sheet is subjected to an ion polishing cross-sectional morphology (CP) test to observe the material type of graphite in the negative electrode active material. As an example, the test method can be: first, the prepared negative electrode sheet is cut into a sample to be tested of a certain size (for example, 2cm×2cm), and the negative electrode sheet is fixed on the sample stage with paraffin. Then the sample stage is placed in the sample holder, locked and fixed, and the power of the argon ion cross-sectional polisher (for example, IB-19500CP) and the vacuum (for example, 10 -4 Pa), set the argon flow rate (e.g. 0.15MPa) and voltage (e.g. 8KV) and polishing time (e.g. 2 hours), adjust the sample stage to the swing mode and start polishing. For sample testing, refer to JY / T010-1996. A random area can be selected from the sample to be tested for scanning testing, and an ion polishing cross-sectional morphology (CP) image of the negative electrode piece can be obtained at a certain magnification (e.g. 5000 times).
[0069] In the embodiment of the present application, the structure of the negative electrode active material (such as artificial graphite particles and carbon layers) can be tested using equipment and methods known in the art. As an example, the following steps S can be followed: select a microgrid of a certain diameter (such as a diameter of 3 mm), clamp the edge of the microgrid with pointed tweezers, and gently place it on a white filter paper with the film surface facing up (the shiny surface, i.e., the film surface, is observed under the light); take an appropriate amount of negative electrode active material sample (such as 1 g) and add it to a beaker containing an appropriate amount of ethanol, and perform ultrasonic oscillation for 10 to 30 minutes; absorb it with a glass capillary, and then drop 2-3 drops of the sample to be tested onto the microgrid; after baking in an oven for 5 minutes, place the microgrid with the sample to be tested on the sample stage, and test it with a transmission electron microscope (such as Hitachi HF-3300SCs-corrected STEM) at a certain magnification (such as 60,000 times), and you can get a transmission electron microscope (TEM) image of the sample to be tested.
[0070] In the embodiments of the present application, primary particles and secondary particles have the meanings known in the art. Among them, primary particles refer to non-agglomerated particles; secondary particles refer to agglomerated particles formed by the aggregation of two or more primary particles. Primary particles and secondary particles can be easily distinguished by taking SEM images using a scanning electron microscope.
[0071] The number ratio of primary particles in the negative electrode active material can be tested by methods known in the art. An exemplary test method is as follows: the negative electrode active material is laid and adhered to the conductive glue to form a sample to be tested with a length × width = 6 cm × 1.1 cm; the particle morphology is tested using a scanning electron microscope (e.g., ZEISS Sigma 300). The test can refer to JY / T010-1996. In order to ensure the accuracy of the test results, multiple (e.g., 5) different areas can be randomly selected from the sample to be tested for scanning testing, and at a certain magnification (e.g., 1000 times), the percentage of the number of primary particles in each area to the total number of particles is calculated, that is, the number ratio of primary particles in the area, and the average value of the test results of multiple test areas is taken as the number ratio of primary particles in the negative electrode active material. In order to ensure the accuracy of the test results, multiple test samples (e.g., 10) can be taken to repeat the above test, and the average value of each test sample is taken as the final test result.
[0072] In the embodiment of the present application, the graphitization degree of the artificial graphite particles in the negative electrode active material is a well-known meaning in the art and can be tested by methods known in the art. For example, an X-ray diffractometer (such as Bruker D8 Discover) can be used, and the test can refer to JIS K0131-1996, JB / T4220-2011, and the d 002 The size of the G is then calculated according to the formula G = (0.344-d 002 ) / (0.344-0.3354)×100% to calculate the graphitization degree, where d 002 It is the interlayer spacing in the graphite crystal structure expressed in nanometers (nm). In X-ray diffraction analysis, a copper target can be used as an anode target, with CuK α The ray is the radiation source, and the wavelength of the ray is The scanning 2θ angle range is 20° to 80°, and the scanning rate may be 4° / min.
[0073] In the embodiments of the present application, the tap density of the negative electrode active material is a well-known meaning in the art and can be tested by methods known in the art. For example, the tap density of the negative electrode active material can be measured with reference to the standard GB / T5162-2006 using a powder tap density tester. For example, the FZS4-4B tap density tester of the Beijing Iron and Steel Research Institute is used, and the test parameters are as follows: vibration frequency: 250±15 times / minute, amplitude: 3±0.2mm, vibration number: 5000 times, measuring cylinder: 25mL.
[0074] In the embodiments of the present application, the gram capacity of the negative electrode active material has a meaning well known in the art and can be tested by methods known in the art. An exemplary test method is as follows: the prepared negative electrode active material as the negative electrode active material, the conductive agent carbon black (SuperP), and the binder polyvinylidene fluoride (PVDF) are mixed uniformly in a solvent N-methylpyrrolidone (NMP) at a mass ratio of 91.6:1.8:6.6 to form a slurry; the prepared slurry is coated on a copper foil current collector, dried in an oven and set aside. A metal lithium sheet is used as the counter electrode, and a polyethylene (PE) film is used as an isolation membrane. Ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed at a volume ratio of 1:1:1, and then LiPF6 is uniformly dissolved in the above solution to obtain an electrolyte, wherein the concentration of LiPF6 is 1 mol / L. CR2430 button batteries are assembled in an argon-protected glove box. After the button cell was left to stand for 12 hours, it was discharged at 0.05C constant current to 0.005V at 25°C, left to stand for 10 minutes, and then discharged at 50μA constant current to 0.005V, left to stand for 10 minutes, and then discharged at 10μA constant current to 0.005V; then it was charged at 0.1C constant current to 2V, and the charging capacity was recorded. The ratio of the charging capacity to the mass of the negative electrode active material is the gram capacity of the prepared negative electrode active material.
[0075] It should be noted that the above-mentioned various parameter tests on the negative electrode active material can be conducted by directly taking samples of the negative electrode active material for testing, or by taking samples from the battery cell for testing.
[0076] When the test sample is sampled from a battery cell, as an example, the sampling can be performed according to the following steps S:
[0077] (1) Discharge the battery cells (for safety reasons, the battery is generally fully discharged); disassemble the battery and remove the negative electrode plates, and soak the negative electrode plates in dimethyl carbonate (DMC) for a certain period of time (e.g., 2 to 10 hours); then remove the negative electrode plates and dry them at a certain temperature and time (e.g., 60°C, 4h), and remove the negative electrode plates after drying.
[0078] (2) The negative electrode sheet dried in step S(1) is baked at a certain temperature and time (e.g., 400° C., 2 h), and a sample of the negative electrode active material is taken from any area of the baked negative electrode sheet (sampling can be performed by scraping powder with a blade).
[0079] (3) The negative electrode active material collected in step S(2) is sieved (for example, using a 200-mesh sieve) to finally obtain a negative electrode active material sample that can be used to test the various material parameters mentioned above in the present application.
[0080] Method for preparing negative electrode active material
[0081] In a second aspect, an embodiment of the present application proposes a method for preparing a negative electrode active material.
[0082] Methods include:
[0083] Step S100, providing artificial graphite particles;
[0084] Step S200, coating the artificial graphite particles to form a carbon layer on at least a portion of the surface of the artificial graphite particles to obtain a negative electrode active material,
[0085] The volume average particle size D of the negative electrode active material is v 50Satisfy: 3μm≤D v 50≤7μm,
[0086] Volume distribution particle size D of negative electrode active material v 1 Satisfaction: D v 1≤1.5μm.
[0087] In some implementations, step S100 may specifically include:
[0088] Step S110, providing coke raw material;
[0089] Step S120, shaping the focused raw material to obtain a precursor;
[0090] Step S130, graphitizing the precursor to obtain artificial graphite particles.
[0091] In step S110 , the coke raw material can be directly purchased from the market, or can be obtained by crushing the coke material.
[0092] In some embodiments, the coke material may be pulverized. The coke material may be pulverized using equipment and methods known in the art, such as a jet mill, a mechanical mill, or a roller mill. The pulverization process often produces a large number of undersized particles, and sometimes oversized particles. Therefore, after pulverization, grading treatment may be performed as required to remove undersized particles and oversized particles in the pulverized powder. After grading treatment, a coke raw material having a desired particle size distribution may be obtained. Grading treatment may be performed using equipment and methods known in the art, such as a grading screen, a gravity classifier, a centrifugal classifier, and the like.
[0093] The pulverization of coke materials can be carried out in a process unit including a pulverizer, a classifier and an induced draft fan. During the pulverization process, the D of the obtained coke raw material can be adjusted by adjusting the feeding frequency, pulverization frequency, classification frequency and induced draft frequency. v 50. D v 1 and D v99 is within the required range. Compared with the lower classification frequency in the traditional crushing process, the method of the present application can increase the classification frequency, which is beneficial to remove too small particles. Compared with the higher induced draft frequency in the traditional crushing process, the method of the present application can reduce the induced draft frequency, which is beneficial to remove too large particles. In addition, compared with the traditional crushing process that controls the frequency within a wider range, the method of the present application can also control the main engine frequency, classification frequency, and induced draft frequency within a narrower frequency range, thereby reducing the particle size distribution width of the coke raw material, for example, regulating the particle size of the coke raw material within a narrower range. The feeding frequency can also be synchronously adjusted to control the feed amount, which can further improve the crushing effect of the material.
[0094] In some embodiments, the coke raw material in step S110 may include one or more of petroleum non-needle coke and petroleum needle coke. Optionally, the coke raw material includes petroleum green coke.
[0095] In some embodiments, in step S120, the coke material may be shaped using equipment and methods known in the art, such as a shaping machine or other shaping equipment.
[0096] In some embodiments, after the coke raw material is shaped, it is further subjected to classification, wherein the classification can be performed using equipment and methods known in the art, such as a classification screen, a gravity classifier, a centrifugal classifier, and the like.
[0097] The shaping and grading treatment can be carried out in a process unit including a shaping machine, a grading machine and an induced draft fan. During the shaping and grading treatment process, the particle size of the obtained precursor can be regulated within the desired range by adjusting the shaping frequency (for example, the main machine frequency and auxiliary machine frequency of the shaping machine), the grading frequency, and the induced draft frequency. Compared with the traditional shaping and grading process, the method of the present application increases the shaping frequency during the treatment process, appropriately extends the shaping time, and also reduces the grading frequency and induced draft frequency during the treatment process, so that the particle size of the obtained precursor is regulated within the target range.
[0098] In some embodiments, in step S130, the precursor is graphitized at a temperature of 2800°C to 3200°C to obtain artificial graphite with an appropriate degree of graphitization. Optionally, the temperature of the graphitization treatment may be 2900°C to 3100°C.
[0099] In step S130, graphitization can be performed using equipment known in the art, such as a graphitization furnace, and further such as an Acheson graphitization furnace. After the graphitization treatment is completed, a small amount of oversized particles agglomerated during the high-temperature graphitization process can be removed by screening, which is beneficial to making the D of the final negative electrode active material v 50. D v 1 and D v 99 is within the required range.
[0100] In some embodiments, step S200 is to coat the artificial graphite particles with an organic carbon source, and to form an amorphous carbon layer on at least a portion of the surface of the artificial graphite particles through heat treatment to obtain a negative electrode active material.
[0101] As an example, the artificial graphite obtained in step S130 can be mixed with an organic carbon source so that the organic carbon source is coated on at least a portion of the surface of the artificial graphite; then, the artificial graphite is heated at a temperature of 700°C to 1800°C to carbonize the organic carbon source and form an amorphous carbon layer on at least a portion of the surface of the artificial graphite. Optionally, the temperature of the heating treatment is 1100°C to 1400°C, and the heating treatment time is 1h to 5h. Optionally, the mass ratio of the artificial graphite to the organic carbon source is 98:2 to 75:25.
[0102] In some embodiments, the organic carbon source can be selected from one or more of asphalt (such as coal tar, petroleum asphalt), phenolic resin, coconut shell, etc., and can further be asphalt.
[0103] In the above preparation process, the coke raw materials usually contain some impurity elements (such as iron, nickel, chromium, zinc, sulfur, silicon, etc.), and the equipment used in the crushing and shaping process will also introduce some impurity elements (such as iron, copper, etc.). Under normal circumstances, the content of impurity elements in the core is very small, generally less than 1ppm.
[0104] In the above preparation process, the organic carbon source used in the coating process and the equipment used for coating will introduce trace amounts of impurity elements into the coating layer.
[0105] Negative electrode
[0106] In a third aspect, the embodiment of the present application further provides a negative electrode sheet, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and including a negative electrode active material, the negative electrode active material includes a negative electrode active material as in any embodiment of the first aspect of the present application, or a negative electrode active material prepared by a method as in any embodiment of the second aspect of the present application. For example, the negative electrode current collector has two surfaces opposite to each other in its thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0107] In some embodiments, the negative electrode active material may further include at least one of natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, silicon-carbon composite, silicon-nitrogen composite and silicon alloy material. The tin-based material may include at least one of elemental tin, tin oxide and tin alloy material.
[0108] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application embodiment has no particular restrictions on the type of the negative electrode conductive agent. As an example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the negative electrode conductive agent is ≤5%.
[0109] In some embodiments, the negative electrode film layer may also optionally include a negative electrode binder. The present application embodiment has no particular restrictions on the type of negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, aqueous acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA) and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder is ≤5% based on the total weight of the negative electrode film layer.
[0110] In some embodiments, the negative electrode film layer may further include other additives. As an example, the other additives may include thickeners, such as sodium carboxymethyl cellulose (CMC-Na), PTC thermistor materials, etc. In some embodiments, based on the total weight of the negative electrode film layer, the mass percentage of the other additives is ≤2%.
[0111] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0112] The negative electrode film layer is usually formed by coating the negative electrode slurry on the negative electrode current collector, drying and cold pressing. The negative electrode slurry is usually formed by dispersing the negative electrode active material, optional conductive agent, optional binder, and other optional auxiliary agents in a solvent and stirring them evenly. The solvent can be N-methylpyrrolidone (NMP) or deionized water, but is not limited thereto.
[0113] The negative electrode plate does not exclude other additional functional layers besides the negative electrode film layer. For example, in some embodiments, the negative electrode plate of the embodiment of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In some other embodiments, the negative electrode plate of the embodiment of the present application further includes a protective layer covering the surface of the negative electrode film layer.
[0114] Battery Cell
[0115] In a fourth aspect, an embodiment of the present application further provides a battery cell.
[0116] A battery cell, also known as a rechargeable battery or storage battery, refers to a battery that can be used continuously by activating the active material by charging after the battery is discharged. Usually, a battery cell includes an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is arranged between the positive electrode sheet and the negative electrode sheet, and mainly plays the role of preventing the positive and negative electrodes from short-circuiting, while allowing active ions to pass through.
[0117] In some embodiments, the battery cell includes the negative electrode sheet of any embodiment of the third aspect of the embodiment of the present application. Thus, the battery cell of the embodiment of the present application can effectively improve the low temperature fast charging capability of the battery cell.
[0118] [Positive electrode]
[0119] The battery cell comprises a positive electrode plate, the positive electrode plate comprises a positive electrode current collector and a positive electrode film layer arranged on at least one side of the positive electrode current collector, and the positive electrode film layer comprises a positive electrode active material.
[0120] The positive electrode active material may include, but is not limited to, at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of lithium-containing transition metal oxides may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of lithium-containing phosphates may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0121] In some embodiments, in order to further improve the energy density of the battery cell, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A fAt least one of lithium-containing transition metal oxides and modified compounds thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes at least one of N, F, S and Cl.
[0122] As an example, the positive electrode active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333), LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622), LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.80 Co 0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.
[0123] In the embodiment of the present application, the modified compound of each positive electrode active material may be a compound that performs doping modification and / or surface coating modification on the positive electrode active material.
[0124] The battery cell will be accompanied by the deintercalation and consumption of active ions such as Li during the charge and discharge process, and the molar content of Li in the battery cell is different when it is discharged to different states. In the list of positive electrode active materials in the embodiments of the present application, the molar content of Li is the initial state of the material, that is, the state before feeding. The positive electrode active material is used in the battery system, and the molar content of Li may change after charge and discharge cycles.
[0125] In the list of positive electrode active materials in the embodiments of the present application, the molar content of oxygen O is only a theoretical value. The release of oxygen from the lattice will cause the molar content of oxygen O to change. In reality, the molar content of oxygen O will fluctuate.
[0126] In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode active material may be 85wt% to 95wt%. Positive electrode active materials in this content range can give the positive electrode sheet a higher capacity and better cycle performance.
[0127] In some embodiments, the positive electrode film layer may further include a positive electrode conductive agent. The present application embodiment has no particular restrictions on the type of the positive electrode conductive agent. As an example, the positive electrode conductive agent includes at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode conductive agent is ≤5%.
[0128] In some embodiments, the positive electrode film layer may also optionally include a positive electrode binder. The present application embodiment has no particular restrictions on the type of positive electrode binder. As an example, the positive electrode binder may include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer and at least one of fluorine-containing acrylic resins. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5%.
[0129] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base and a metal material layer formed on at least one surface of the polymer material base. As an example, the metal material of the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy. As an example, the polymer material base may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS) and polyethylene (PE).
[0130] The positive electrode film layer is usually formed by coating the positive electrode slurry on the positive electrode current collector, drying and cold pressing. The positive electrode slurry is usually formed by dispersing the positive electrode active material, optional conductive agent, optional binder and any other components in a solvent and stirring them uniformly. The solvent can be N-methylpyrrolidone (NMP), but is not limited thereto.
[0131] [Electrolyte]
[0132] In some embodiments, the battery cell further includes an electrolyte.
[0133] During the charge and discharge process of the battery cell, active ions are embedded and released back and forth between the positive electrode and the negative electrode, and the electrolyte plays a role in conducting active ions between the positive electrode and the negative electrode. The embodiment of the present application has no particular limitation on the type of electrolyte, which can be selected according to actual needs.
[0134] The electrolyte includes electrolyte salt and solvent. The types of electrolyte salt and solvent are not specifically limited and can be selected according to actual needs.
[0135] As an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0136] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate, methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0137] In some embodiments, the electrolyte may also optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high temperature performance, and additives that improve battery low temperature power performance.
[0138] [Isolation film]
[0139] In some embodiments, the battery cell further includes a separator. The embodiments of the present application have no particular restrictions on the type of separator, and any known porous separator with good chemical stability and mechanical stability can be selected.
[0140] In some embodiments, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene and polyvinylidene fluoride. The isolation membrane may be a single-layer film or a multi-layer composite film, without particular limitation. When the isolation membrane is a multi-layer composite film, the materials of each layer may be the same or different, without particular limitation.
[0141] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly by a winding process and / or a lamination process.
[0142] In some embodiments, the battery cell may include an outer packaging, which may be used to encapsulate the electrode assembly and the electrolyte.
[0143] In some embodiments, the outer packaging of the battery cell may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the battery cell may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT) and polybutylene succinate (PBS).
[0144] The present application embodiment has no particular limitation on the shape of the battery cell, which may be cylindrical, square or any other shape. Figure 1 The battery cell 5 is a square structure as an example.
[0145] In some embodiments, Figure 2 As shown, the outer package may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can form an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is infiltrated in the electrode assembly 52. The number of electrode assemblies 52 contained in the battery cell 5 can be one or more, which can be adjusted according to demand.
[0146] The preparation method of the battery cell of the embodiment of the present application is well known. In some embodiments, the positive electrode sheet, the separator, the negative electrode sheet and the electrolyte can be assembled to form a battery cell. As an example, the positive electrode sheet, the separator and the negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process, and the electrode assembly is placed in an outer package, and the electrolyte is injected after drying, and the battery cell is obtained through vacuum packaging, standing, forming, shaping and other processes.
[0147] In some embodiments of the embodiments of the present application, the battery cells according to the embodiments of the present application can be assembled into a battery module. The number of battery cells contained in the battery module can be multiple, and the specific number can be adjusted according to the application and capacity of the battery module.
[0148] Figure 3 FIG. 4 is a schematic diagram of a battery module 4 as an example. Figure 3 As shown, in the battery module 4, the plurality of battery cells 5 may be arranged in sequence along the length direction of the battery module 4. Of course, they may also be arranged in any other manner. Further, the plurality of battery cells 5 may be fixed by fasteners.
[0149] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of battery cells 5 are received in the receiving space.
[0150] In some embodiments, the battery modules can also be assembled into a battery pack, and the number of battery modules contained in the battery pack can be adjusted according to the application and capacity of the battery pack. Battery cells, battery modules, and battery packs can all be used as examples of batteries.
[0151] Figure 4 and Figure 5 FIG. 1 is a schematic diagram of a battery pack 1 as an example. Figure 4 and Figure 5 As shown, the battery pack 1 may include a battery box and a plurality of battery modules 4 disposed in the battery box. The battery box includes an upper box body 2 and a lower box body 3, wherein the upper box body 2 is used to cover the lower box body 3 and form a closed space for accommodating the battery modules 4. The plurality of battery modules 4 may be arranged in the battery box in any manner.
[0152] Electrical devices
[0153] In a fifth aspect, the embodiments of the present application provide an electrical device, which includes at least one of the battery cells, battery modules or battery packs of the embodiments of the present application. The battery cells, battery modules or battery packs can be used as power sources for electrical devices, or as energy storage units for electrical devices. Electrical devices can be, but are not limited to, mobile devices (such as mobile phones, laptops, etc.), electric vehicles (such as pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.), electric trains, ships and satellites, energy storage systems, etc.
[0154] The electrical device can select a battery cell, a battery module or a battery pack according to its usage requirements.
[0155] Figure 6 Schematic diagram of an exemplary electric device 6. The electric device 6 is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle, etc. In order to meet the requirements of the electric device 6 for high power and high energy density, a battery pack or a battery module may be used.
[0156] As another example, the electric device may be a mobile phone, a tablet computer, a notebook computer, etc. The electric device is usually required to be light and thin, and a battery cell may be used as a power source.
[0157] Example
[0158] The following examples more specifically describe the contents disclosed in the embodiments of the present application, and these examples are only for illustrative purposes, because it is obvious to those skilled in the art that various modifications and changes are made within the scope of the disclosure of the embodiments of the present application. Unless otherwise stated, all parts, percentages and ratios reported in the following examples are based on mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0159] Example 1 Preparation of lithium ion battery
[0160] 1. Preparation of negative electrode sheet
[0161] Preparation of negative electrode active materials
[0162] The raw petroleum coke is crushed to obtain the coke raw material. The coke raw material is shaped and graded to obtain the precursor.
[0163] The precursor is graphitized at a temperature of 3000°C and sieved to obtain artificial graphite. The artificial graphite is then coated with organic carbon source pitch and carbonized to obtain a negative electrode active material, which includes artificial graphite particles and a carbon layer located on at least a portion of the surface of the artificial graphite particles. The negative electrode active material is a primary particle.
[0164] Preparation of negative electrode
[0165] The negative electrode active material, conductive agent carbon black (SuperP), thickener sodium carboxymethyl cellulose (CMC-Na), and binder styrene-butadiene rubber (SBR) are fully stirred and mixed in an appropriate amount of solvent deionized water at a weight ratio of 96.4:1:1.2:1.4 to form a uniform negative electrode slurry; the negative electrode slurry is evenly coated on the surface of the negative electrode current collector copper foil, and after drying and cold pressing, a negative electrode sheet is obtained.
[0166] 2. Preparation of positive electrode
[0167] Aluminum foil was used as the positive electrode current collector.
[0168] The positive electrode active material LiNi 0.5 Co 0.2 Mn 0.3 O2 (NCM523), conductive agent carbon black, and binder polyvinylidene fluoride (PVDF) are fully stirred and mixed in a proper amount of solvent N-methylpyrrolidone NMP at a weight ratio of 90:5:5 to form a uniform positive electrode slurry; the positive electrode slurry is evenly coated on the surface of the positive electrode current collector aluminum foil, and after drying and cold pressing, a positive electrode sheet is obtained.
[0169] 3. Isolation film
[0170] A porous polyethylene (PE) film is used as the isolation membrane.
[0171] 4. Preparation of electrolyte
[0172] In an environment with a water content of less than 10 ppm, non-aqueous organic solvents ethylene carbonate EC, ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an electrolyte solvent, and then the lithium salt lithium hexafluorophosphate and the electrolyte solvent are mixed to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0173] 5. Preparation of battery cells
[0174] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then they are wound to obtain an electrode assembly; the electrode assembly is placed in an outer packaging shell, and after drying, the electrolyte is injected, and after vacuum packaging, standing, forming, shaping and other processes, a lithium-ion battery is obtained.
[0175] Comparative Example 1 and Comparative Example 2
[0176] A lithium ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the particle size of the negative electrode active material in Example 1 was adjusted, especially D v 50.
[0177] Example 2-1 to Example 2-8
[0178] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the particle size of the negative electrode active material in Examples 2-1 and 2-3 was adjusted.
[0179] Example 3-1 to Example 3-5
[0180] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the tap density of the negative electrode active material in Examples 3-1 to 3-5 was adjusted.
[0181] Example 4-1 to Example 4-3
[0182] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the graphitization degree of the artificial graphite particles of the negative electrode active material in Examples 4-1 to 4-3 was adjusted.
[0183] Example 5-1 to Example 5-2
[0184] A lithium-ion battery was prepared by a method similar to that of Example 1. The difference from Example 1 was that the average thickness of the carbon layer of the negative electrode active material in Example 5-1 and Example 5-2 was adjusted.
[0185] The relevant parameters of the embodiments and comparative examples are shown in Table 1 below.
[0186] Performance Testing
[0187] 1. Performance test of lithium-ion batteries
[0188] At -10°C, the lithium-ion battery prepared in the embodiment and the comparative example was adjusted to 80% SOC, charged at 20C for 5s, discharged at 20C for 5s, and cycled for 500 cycles. The lithium-ion battery was then fully charged at 0.33C at room temperature and disassembled to observe the lithium deposition state on the surface of the negative electrode. Among them, the lithium deposition area on the surface of the negative electrode is less than 5%, which is considered as slight lithium deposition, the lithium deposition area is 5% to 40%, which is considered as moderate lithium deposition, and the lithium deposition area is greater than 40%, which is considered as severe lithium deposition.
[0189] Test Results
[0190] The test results are shown in Table 1.
[0191] Table 1
[0192]
[0193] It can be seen from Table 1 that the D of the negative electrode active material in Comparative Example 1 v 50 and D v 1 are both large. Under low temperature conditions, the polarization of the battery increases, the active specific surface area of the negative electrode interface reaction decreases, and the lithium ions transferred to the surface of the negative electrode cannot participate in the interface reaction in time, resulting in easy lithium precipitation at the interface. In addition, due to D v 50 is larger, the transmission distance of lithium ions increases under high SOC state, and the low temperature charging capability deteriorates.
[0194] Comparative Example 2 D v 1 is larger, and the content of fine powder in the negative electrode active material is less, which is not conducive to the rapid transfer of lithium ions and electrons under high SOC state, while D v The larger value of 99 makes the consistency of lithium embedding in particles relatively poor, which easily aggravates the polarization phenomenon and is not conducive to the rapid charging of battery cells.
[0195] Compared with Comparative Examples 1 and 2, and combined with Figure 7 and Figure 8 , the embodiment of the present application adjusts the D of the negative electrode active material v 99.D v 50 and D v1 Within an appropriate range, it can improve the lithium ion diffusion rate while improving the consistency of lithium insertion, thereby improving the low-temperature fast charging performance of the battery cell.
[0196] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.
Claims
1. A negative electrode active material comprising artificial graphite particles and a carbon layer disposed on at least a portion of the surface of the artificial graphite particles, wherein: The volume average particle size D of the negative electrode active material v 50Satisfy: 3μm≤D v 50≤7μm; The volume distribution particle size D of the negative electrode active material v 1 Satisfaction: D v 1≤1.5μm.
2. The negative electrode active material according to claim 1, wherein: 0.8μm≤D v 1≤1.5μm; optionally, 0.9μm≤D v 1≤1.3μm; further optionally, 0.9μm≤D v 1≤1.0μm.
3. The negative electrode active material according to claim 1 or 2, wherein: D v 99≤18μm; optionally, 12μm≤D v 99≤18μm.
4. The negative electrode active material according to any one of claims 1 to 3, wherein The negative electrode active material includes primary particles, and the primary particles account for ≥90% of the negative electrode active material; optionally, ≥95%.
5. The negative electrode active material according to any one of claims 1 to 4, wherein: The gram capacity of the negative electrode active material is 330 mAh / g to 340 mAh / g; and / or The tap density of the negative electrode active material is 0.78 g / cm 3 Up to 1.2g / cm 3 .
6. The negative electrode active material according to any one of claims 1 to 5, wherein: The graphitization degree of the artificial graphite particles is 90% to 93%; optionally 91% to 93%.
7. The negative electrode active material according to any one of claims 1 to 6, wherein: The average thickness of the carbon layer is ≥2 nm, and can be selected to be 2 nm to 20 nm.
8. A negative electrode sheet, comprising a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material, wherein the negative electrode active material comprises the negative electrode active material according to claim 1 to claim 7.
9. A battery comprising the negative electrode sheet as claimed in claim 8.
10. An electrical device comprising the battery according to claim 9.
Citation Information
Patent Citations
Silicon negative pole piece, preparation method thereof and lithium ion battery
CN112542570A
Secondary battery and manufacturing method therefor, and apparatus comprising secondary battery
CN113875051A
Anode active material and lithium seceondary battery comprising the same
CN114068924A
Negative electrode for secondary battery and secondary battery comprising same
CN114430021A
Negative active material, method for preparing same, secondary battery, and battery module, battery pack and device including secondary battery
CN114730875A